CARBON STORED ON SEAGRASS BEDS IN GILI MARINGKIK, LOMBOK, INDONESIA - Firman Ali Rahman; Ibnul Qayim; Yusli Wardiatno (SEAMEO BIOTROP, 2023)
Seagrass beds are an important vegetation for reducing the impact of global warming besides the function of forest and mangroves vegetation. The research aims to find the composition of seagrass species, density, seagrass coverage, seagrass standing biomass, seagrass standing carbon and substrate carbon. The research was conducted in Gili Maringkik, Lombok, Indonesia. The research included observation of species composition and the sample was collected from 0.5 ×0.5 m plot area. Total plot area was 25 on five lanes with the space between plots 25 m and between lanes 100 m. The researcher found that there were eight seagrass species (two families, six genera): Cymodocea rotundata, Cymodocea serrulata, Enhalus acoroides, Halodule pinifolia, Halophila minor, Halophila spinulosa, Syringodium isoetifolium and Thalassia hemprichii. Cymodocea rotundata (506.40±187.809 stand.m-2) was the species of highest density and while the species of Thalassia hemprichii (36.52±30.004 %) was the species of highest coverage. Total of seagrass standing biomass in Gili Maringkik was 1081.85 g.DW.m-2 with the carbon stock of seagrass beds was 483.86 g.C.m-2 and substrate carbon content was 0.09%–0.49%. the total carbon stock of seagrass beds in Gili Maringkik has 153.96 ton.C (4.84 ton.C.Ha-1).